FACTORS INFLUENCING THE PURCHASE INTENTION OF HEALTH INSURANCE IN KOTA KINABALU SABAH - Violeta Wilfred, (Malaysian Journal of Business and Economics (MJBE), 2020)
Health and life insurance have been very critical issue in today’s world. Insurance has become a major necessity for everyone to have in order to protect them or their family from any unforeseen circumstances in life. This study is done to find out what is the factors that influencing the purchase of health and life insurance to the public as well as to determine the relationship among these variables. This descriptive and quantitative study uses 200 respondents selected using a random sampling method from clients of CIMB Bank Branches around Kota Kinabalu, Sabah. IBM SPSS 23.0 was used to analyse data gathered from a self-administered questionnaire. Findings showed that the intention to purchase was perceived moderately. This study also showed that income level, knowledge level, income protection, risk attitude and social factors are significantly, positively and strongly related to purchase intention of life and health insurance.